The Effect of Thalidomide on Bleomycin-Induced Pulmonary Fibrosis in Rats - Shahram Rafieian; Sayyed Ali Alavi; Nooshin Mirkheshti; Atefeh Sadeghizadeh (مجله دانشکده پزشکی اصفهان, 2009)
Background: Current evidences suggest that the change in cytokine level by induction of angiogenesis may play a key role in the development of lung fibrosis. It seems, thalidomide by the destruction of endothelial cells and changing TNF-α level could be helpfull in antiangiogenic therapies. The present study examined the effect of thalidomide on bleomycin-induced lung fibrosis in rats. Methods: 18 rats were divided into three groups: (group 1) negative control group, which received normal saline intratracheally, (group 2) positive control group in which bleomycin was intratracheally injected, (3) intervention group which recieved thalidomide and bleomycine. Lung tissue was extracted after one month of treatment. Collagen content (as fibrosis index) and angiogenesis were indicated by Woessner method and Von Wilbrand staining, respectively. Total Lung Capacity index, was determined by MATLAB software. Findings: Collagen content had significant difference between positive and negative control groups, but there was no difference between positive control and experimental group. There was no significant difference between groups for angiogenesis and Total Lung Capacity index. Conclusion: Thalidomide had no effect on bleomycin induced pulmonary fibrosis. Otherwise, the findings of the study provide this evidence that thalidomide may induce pulmonary injury that is pathologically looks like IPF. So, more studies with some other angiostatic drugs and different doses are needed. Key words: Pulmonary fibrosis, Thalidomide, Bleomycin, Angiogenesis.